Learn microservices with Spring Boot : a practical approach to RESTful Services using RabbitMQ, Eureka, Ribbon, Zuul and Cucumber - Macero, Moises (Apress, 2017)
Build a microservices architecture with Spring Boot, by evolving an application from a small monolith to an event-driven architecture composed of several services. This book follows an incremental approach to teach microservice structure, test-driven development, Eureka, Ribbon, Zuul, and end-to-end tests with Cucumber. Author Moises Macero follows a very pragmatic approach to explain the benefits of using this type of software architecture, instead of keeping you distracted with theoretical concepts. He covers some of the state-of-the-art techniques in computer programming, from a practical point of view. You?ll focus on what's important, starting with the minimum viable product but keeping the flexibility to evolve it. You will: Build microservices with Spring Boot Use event-driven architecture and messaging with RabbitMQ Create RESTful services with Spring Master service discovery with Eureka and load balancing with Ribbon Route requests with Zuul as your API gateway Write end-to-end rests for an event-driven architecture using Cucumber Carry out continuous integration and deployment.